The use of Web 2.0 tools in English language learning: A systematic review - Genç, Gülten; Kırmızıbayrak, Özge (Malque Publishing, 2024)
This study attempts to systematically review the incorporation of Web 2.0 tools into the English Language Learning (ELL) context. It explores the impacts, methodological decisions, and focus areas that distinguish this developing subject through a comprehensive review of research papers spanning many dimensions. From the Eric database, papers on Web 2.0 use in English language education that were published between 2018 and 2022 were chosen. In this context, sixty-two pieces reviewed a rigorous evaluation based on a set of standards. The research results reveal a wide range of benefits connected to technological integration, including improved motivation and teamwork. The results of the systematic analysis highlight the need for a flexible and nuanced approach to technology integration in ELL and offer insightful recommendations for practitioners, academics, and learners. © 2024, Malque Publishing. All rights reserved.
Keywords: systematic review; teaching english as a foreign language; technology in language education; web 2.0 tools